The efficacy and acceptability of electroconvulsive therapy for treating borderline personality disorder symptoms with or without comorbid disorders: a systematic review - Mohammad A. Abu Sabra; Andaleeb M. Abu Kamel; Mohammad R. Alosta; Elham H. Othman (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Borderline personality disorder (BPD) is a mental illness connected with various mental disorders as a comorbid condition that affects an individual's capacity to live a healthy life. Electroconvulsive therapy (ECT) is a crucial medical intervention approach that can effectively alleviate the resistant symptoms of BPD, with or without comorbidity. Despite ECT being a safe and low-risk procedure, its utilization in treating BPD is limited and debatable. This review aims to investigate the efficacy and acceptability of electroconvulsive therapy for treating borderline personality disorder symptoms with or without comorbid disorders. Results We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to screen 1150 studies published between 2000 and 2024 from various databases. A total of nine studies that fulfilled the eligibility criteria reported that ECT has positive benefits and impacts on a variety of health-related aspects of life for patients with BPD symptoms, whether or not they also have comorbid disorders. This means that ECT may have a beneficial effect on reducing the severity of symptoms and play a significant role in the treatment outcomes of patients. Conclusions ECT is a promising treatment that is recognized as a credible treatment approach for ensuring long-term positive outcomes in individuals with BPD. It requires ongoing support from stakeholders, legislators, and community support networks to improve practitioners' proficiency and modify clinical practice standards to achieve better results.